Chromosomal deletions in myelodysplasia. - Boultwood, J; Fidler, C (1995)
There are two major classes of genes implicated in human tumorigenesis, the oncogenes and the tumour suppressor genes. In haematological malignancies most emphasis has been placed upon the recurring translocations in which the juxtaposition of two gene sequences has resulted in the activation of an oncogene. Chromosomal loss rather than translocation is the most frequent karyotypic abnormality in the myelodysplastic syndromes, a heterogeneous group of clonal malignant blood disorders characterised by dyshaematopoiesis and/or impaired maturation of haemopoietic cells with frequent evolution to acute leukaemia. Recent attention has focused on the loss of genetic material as a result of chromosomal monosomy or deletion in the myelodysplastic syndromes. The most frequently reported deletions in these myeloid syndromes are of chromosomes 5, 20 and 7. Deletions of chromosomes 11, 12, and 13, although more rarely observed, are also characteristics of the myelodysplastic syndromes. It is probable that the deleted chromosomal bands give the location for as yet unidentified myeloid specific tumour suppressor loci and there is considerable interest in the cloning of these genes. This review discusses the three most frequently observed deletions in MDS; 7q deletion, 5q deletion and 20q deletion taking into account recent evidence on the respective critical regions of gene loss and the role of candidate genes.